Combustion of pelletized empty fruit bunch and oil palm shell in a swirling fluidized bed combustor - Othaman, Muhamad Fazli (2018)
Climate change and its associated impact has been one of the biggest challenge to mankind today. Alternative fuels are therefore sought to reduce the amount of greenhouse gases emission which was believed to be the main reason for global warming. In countries like Malaysia, biomass is available in abundance thus making it the preferred alternative fuel in comparison to other sources. One of the popular means of biomass combustion is through fluidized bed system. At present, conventional fluidized bed only provides fluidization air from the distributor at the bottom. This technique has its drawbacks such as the non-uniform temperature distribution inside the bed due to momentum transfer in axial direction only. This drawback however, can be addressed by introducing the swirling fluidized bed which provides inclined injection of air inside the fluidized bed. In this study, an innovative combustion technique for biomass is proposed, designated as the Swirling Fluidized Bed Combustor (SFBC). The SFBC provides excellent solid-air mixing which is ideal for combustion, by using annular-blade distributor. Two types of biomass from oil palm was studied, namely the pelletized empty fruit bunch (PEFB) and oil palm shell (OPS). The ultimate and proximate analysis were investigated for both biomass before combustion experiments were carried out in the SFBC. The effect of excess air was studied at four different volume percentages of 16.55%, 20.07%, 27.91% and 35.82% at constant biomass feed rate of 54.26 kglh for PEFB and 48.91 kg/h for OPS. Emissions of CO, C02 and NOx measured during combustion shows that the SFBC system is capable in reducing the CO and NOx for all excess air provided. The emission however C02 increased, indicating better conversion taking place in the SFBC. An average combustion efficiency of98.4% was obtained for PEFB and 99.5% for OPS, showing the potential to utilize SFBC in commercial scale in Malaysia.